Joint quantity/quality management of groundwater - Roseta-Palma, C. (Environmental and Resource Economics, 2003)
Economic literature on groundwater management has traditionally been split into two areas: there are papers that evaluate different schemes of dynamic aquifer management, considering that pumping costs vary with stock but ignoring water quality. On the other hand, there are papers that consider contamination problems caused by specific pollutants. This paper presents two alternative models for joint quantity-quality management, and it shows that existing models are in fact special cases of these. The framework is dynamic and considers both the stock of water quantity and a stock measure of water quality. Optimal taxes are derived, and shown to be different from those in existing quantity-only or quality-only models. Implementation problems are briefly discussed.